PYTHOCHEMICAL SCREENING OF Musa acuminata STEM WATER EXTRACT - Amy Nindia Carabelly; Didit Aspriyanto (FKG Unlam, 2020)
Background: Regenerative therapy has been progressing into the utilization of mesenchymal stem cell (MSC). Nevertheless, the limited number of MSC has put growth factor as an essential supplement for cell culture media yet relatively unaffordable because highly priced. Alternative compound which cost reasonably is required. Exogenous phytochemical material in herbal plant extract may increase the number of MSC, one of which is mauli banana stem. Purpose: To analyze secondary metabolites identified in mauli banana stem water extract. Method: Mauli banana stem was macerated using water solvent to be analyzed qualitatively for alkaloid, tannin, flavonoid, saponin, terpenoid, diterpen and steroid. Screening was followed by quantitative analysis to determine the total of alkaloid, flavonoid, condensed tannin and hydrolysable tannin. Result: Secondary metabolite compounds of mauli banana stem water extract were alkaloid (4.15%), hydrolysable tannin (1.055%), condensed tannin (0.42%) and flavonoid (0.31%). Conclusion: Mauli banana stem water extract has potential as alternative growth factor to increase the number of MSC in vitro.